Description of Self-Efficacy of Female Prisoners Facing Community Stigma after Release: A Case Study - Sonetha Astilina Blegur; Megah Andriany; Nur Setiawati Dewi (GLOBAL HEALTH SCIENCE GROUP, 2025)
The negative effects of stigma can cause anxiety in WBP, fear, low self-efficacy to re-adapt and even increase the number of recidivists due to the pressure of stigma experienced. Previous research examined the self-adjustment of former WBPs facing stigma after release, however, research on the self-efficacy of female WBPs in facing public stigma is still very limited, therefore researchers are interested in conducting research related to the self-efficacy of female prisoners in facing stigma in society. Objective: To describe the self-efficacy of female prisoners in facing stigma in the community after being released from prison. Methods: This study is a descriptive qualitative study to describe the self-efficacy of female prisoners in facing community stigma. Three participants were selected using purposive sampling and met the criteria of female prisoners who were willing to be participants and female prisoners who would be released in less than one year. The research was conducted at the Women's Correctional Center Class II A Semarang. Data collection was conducted through in-depth interviews and completed with field notes, according to the place agreed upon by the research and participants. Interviews were recorded then made verbatim transcripts and analyzed using the qualitative descriptive analysis method according to Miles and Huberman. Results: Two main themes were identified: the first theme was not caring and persevering in adversity, the second theme was working and realizing great expectations. Conclusion: The results showed that female prisoners who will be released show an attitude of not caring about the stigma they may face after returning to society, because they have confidence in their ability to overcome existing challenges. High self-efficacy plays an important role in helping female prisoners stay focused on their goals, such as finding a job or starting a new business, without being affected by negative views or stereotypes from society.